Effect of family members′ voice on level of consciousness of comatose patients admitted to the intensive care unit: A single-blind randomized controlled trial - Hossein Tavangar; Manijeh Shahriary-Kalantary; Tahereh Salimi; Mohammadhossein Jarahzadeh; Mohammadtaghi Sarebanhassanabadi (Advanced Biomedical Research, 2015)
Background: Coma is one of the most important complications of brain injury. Comatose patients in the intensive care units are exposed to sensory deprivation. This study aims to survey the effect of family members′ voice on level of consciousness of comatose patients hospitalized in the intensive care units. Materials and Methods : In this single-blind randomized controlled trial, 40 comatose patients with brain injury with acute subdural hematoma in intensive care units were randomly assigned into two groups. The intervention group was stimulated twice a day each time 5-15 min with a recorded MP3 from family members′ voice for 10 days. The patients′ level of consciousness was measured with Glasgow Coma Scale before and after auditory stimulations. In the control group, GCS was measured without auditory stimulation with the same time duration like intervention group. Data analysis in software SPSS version 15 and using Chi-square test, independent t-test, paired t- test and analysis of variance with repeated measures was done. Results: On the first day before the intervention, there was no a statistically significant difference between the mean of GCS in both groups (P = 0.89), but on the tenth day after the intervention, there was a significant difference (P = 0.0001) between the mean GCS in both control and intervention groups. Also, there was a significant difference between the mean daily GCS scores in two groups (P = 0.003). The findings during ten days showed the changes in the level of consciousness in the intervention group from the 4 rd day of the study were more in the mean daily GCS scores than control group. Conclusion : This study indicated that family members′ voice can increase level of consciousness of comatose patients with acute subdural hematoma.